2012
DOI: 10.1111/j.1365-2702.2011.04048.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of a new instrument to measure disease self‐management of the early stage chronic kidney disease patients

Abstract: The CKD-SM instrument is useful for clinicians who wish to identify the problems with self-management among chronic kidney disease patients early. Self-management assessment will be helpful to develop intervention tailored to the needs of the chronic kidney disease population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(81 citation statements)
references
References 11 publications
(25 reference statements)
1
79
1
Order By: Relevance
“…Chronic kidney disease self-management has a substantial number of daily tasks that a person needs to perform to manage the impact of the disease and to slow its progression (Curtin, Mapes, & Thomas-Hawkins, 2001;Lin, Wu, Wu, Chen, & Chang, 2012;Ong, Jassal, Porter, Logan, & Miller, 2013). The following sections review the previously described skills in the context of the CKD self-management.…”
Section: Skillsmentioning
confidence: 99%
See 4 more Smart Citations
“…Chronic kidney disease self-management has a substantial number of daily tasks that a person needs to perform to manage the impact of the disease and to slow its progression (Curtin, Mapes, & Thomas-Hawkins, 2001;Lin, Wu, Wu, Chen, & Chang, 2012;Ong, Jassal, Porter, Logan, & Miller, 2013). The following sections review the previously described skills in the context of the CKD self-management.…”
Section: Skillsmentioning
confidence: 99%
“…In addition, Lin et al (2012) and Ong et al (2013) have indicated other components also needed in self-management in people with CKD. Lin et al (2012) used Lorig and Holman (2003) components of self-integration, problem solving, social support, and taking action.…”
Section: 42mentioning
confidence: 99%
See 3 more Smart Citations